CANCER-RELATED FATIGUE IN CHILDREN WITH CANCER - Mariyana, Rina; Febrina, Cory (Universitas Fort De Kock, 2025)
Introduction: Children with cancer are susceptible to experiencing symptoms of anxiety, nausea, vomiting, nutrition, fatigue, sleep disorders and pain. Children often experience fatigue during the treatment process. not much is known about other factors that influence the experience of fatigueAim: This study aimed to determine fatigue data in children with cancer that explains aspects of the experience of fatigue, with a focus on interoceptive awareness and emotional vulnerability. Method: This research uses a cross sectional study approach. The subjects of this study were 64 people with the inclusion criteria of children with cancer, respondents aged 6-18 years, patients who signed informed consent, were willing to be respondents, and were undergoing treatment. The sampling technique used accidental sampling using 64 respondents. Fatigue and quality of life were measured using the FAS (Fatigue Assessment Scale) PedsQol Cancer Module 3.0. In data analysis using chi square.Findings: The results of the research were that there was a relationship between fatigue and quality of life in children with cancer (ρ=0.000), and showed that 20 children (31.2%) experienced severe fatigue, while 18 children (28.1%) had quality of life. bad. HConclusion and recommendation: based on this research that Keywords: children with cancer, fatigue, quality of life Introduction: Children with cancer are susceptible to experiencing symptoms of anxiety, nausea, vomiting, nutrition, fatigue, sleep disorders and pain. Children often experience fatigue during the treatment process. not much is known about other factors that influence the experience of fatigueAim: This study aimed to determine fatigue data in children with cancer that explains aspects of the experience of fatigue, with a focus on interoceptive awareness and emotional vulnerability. Method: This research uses a cross sectional study approach. The subjects of this study were 64 people with the inclusion criteria of children with cancer, respondents aged 6-18 years, patients who signed informed consent, were willing to be respondents, and were undergoing treatment. The sampling technique used accidental sampling using 64 respondents. Fatigue and quality of life were measured using the FAS (Fatigue Assessment Scale) PedsQol Cancer Module 3.0. In data analysis using chi square.Findings: The results of the research were that there was a relationship between fatigue and quality of life in children with cancer (ρ=0.000), and showed that 20 children (31.2%) experienced severe fatigue, while 18 children (28.1%) had quality of life. bad. HConclusion and recommendation: based on this research that Keywords: children with cancer, fatigue, quality of life